Abnormal Functional Hierarchies of EEG Networks in Familial and Sporadic Prodromal Alzheimer's Disease During Visual Short-Term Memory Binding - Smith, Keith M.; Starr, John M.; Escudero, Javier; Ibañez, Agustin; Parra, Mario A. (Frontiers in Neuroimaging, 2022)
Background: Alzheimer’s Disease (AD) is associated with both hierarchical alterations of functional dependencies between brain regions and a decreased ability to perform Visual Short-Term Memory Binding (VSTMB) tasks. Familial AD, being genetically determinable, is often used to model the pre-clinical phase of the prevalent sporadic AD in the elderly. Yet familial AD develops in middle age and possible complications due to ageing in AD is underexplored. We undertake to study these issues utilising recently proposed network characterisations of complex hierarchical brain function. Methods: Electroencephalogram (EEG) signals were recorded during the performance of Visual Short-Term Memory (VSTM) tasks by familial AD patients (E280A mutation of the presenilin-1 gene) and elderly MCI patients at high risk of sporadic AD, alongside age-matched healthy controls. Functional connectivity was computed using the phase-lag index in Alpha and Beta and network analysis was employed using network indices of hierarchical spread (degree variance) and hierarchical complexity. Results: Hierarchical characteristics of EEG functional connectivity networks revealed abnormal patterns in familial MCI VSTMB function and sporadic MCI VSTMB function. The middle-aged familial MCI binding network displayed a larger hierarchical spread in lower Beta compared to healthy controls (p = 0.0051, Cohen’s d = 1.0124), while the elderly sporadic MCI binding network displayed greater hierarchical complexity in Alpha (p = 0.0140, Cohen’s d = 1.1627). Characteristics in healthy ageing were not shown to differ. Conclusions: Decreased performance of VSTM binding in early-stage AD is associated with aberrant hierarchical patterns of functional connectivity. Differences in these patterns between familial and sporadic AD suggest cross-frequency complications with ageing characterised by increased heterogeneity of node roles in the functional hierarchy.